2017
DOI: 10.1016/j.juro.2017.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pediatric Percutaneous Nephrolithotomy Outcomes Using Contemporary Scoring Systems

Abstract: The scoring systems analyzed could be used to predict success of percutaneous nephrolithotomy in the pediatric setting. However, further studies are needed to formulate modifications for use in children. The main variables in the scoring systems, ie stone burden, tract length and case volume, were measured using records from adult patients. Besides these variables, the relatively small pelvicalyceal system and higher incidence of anatomical malformations in children could potentially affect percutaneous nephro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Several studies 20,21 have evaluated the applicability of the contemporary PCNL scoring systems of adults in pediatric patients and found that the S.T.O.N.E. score and Guy's score demonstrated the greatest accuracy in predicting SFR and CR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 20,21 have evaluated the applicability of the contemporary PCNL scoring systems of adults in pediatric patients and found that the S.T.O.N.E. score and Guy's score demonstrated the greatest accuracy in predicting SFR and CR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients, 58.3% were male and 41.7% were female. The mean BMI value was 27.2 (23)(24)(25)(26)(27)(28)(29)(30)(31) kg/m 2 . There was hypertension in 35% of the patients and diabetes mellitus in 25%.…”
Section: Resultsmentioning
confidence: 98%
“…( p < 0.001 with an AUC of 0.671), and GSS ( p = 0.019 with an AUC of 0.629) on multivariate logistic regression analysis [26]. Recent studies evaluating the predictive value of stone scoring systems among special patient groups, such as pediatric patients and those with obesity, staghorn stones, and chronic kidney disease, revealed controversial results [27-30]. Taking this into account, we believe that the efficacy of stone scoring systems differs among patients with special conditions.…”
Section: Discussionmentioning
confidence: 99%